2020
DOI: 10.1021/acs.jpcc.0c07415
|View full text |Cite
|
Sign up to set email alerts
|

Poly-p-phenylenes as Novel Bulk-type Anode Materials for Potassium-Ion Batteries: A First-Principles Study

Abstract: Because of the high voltage and low cost, potassium-ion batteries have become a hotspot in the research of rechargeable batteries. In this paper, the electrochemical properties of poly-p-phenylenes are studied based on first-principles calculations. Poly-p-phenylenes are predicted to be promising intercalation-type anode materials for potassium-ion batteries that are superior to graphite. The results show that potassium ions can intercalate into poly-p-phenylenes without significant phase change. The anode is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The interlayer study for Ti 3 C 2 is shown in Figure S14, the interlayer spacing increase is 0.49 Å, and the expansion ratio is about 5.0%, which is larger than that of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 with one layer of Zn atoms and comparable with that of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 with four layers of Zn atoms. The 5.8% expansion ratio is less than the values of graphene-molybdenum disulfide (34%) and poly p -phenylenes (60%) and comparable with the value of Y 2 CF 2 (5.2%) in recent reports. The small volume expansion of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 indicates its structural stability with zinc-ion adsorption/desorption, potentially large charge/discharge cycles, and long lifetime, which is significant for rechargeable zinc-ion batteries.…”
Section: Resultssupporting
confidence: 67%
“…The interlayer study for Ti 3 C 2 is shown in Figure S14, the interlayer spacing increase is 0.49 Å, and the expansion ratio is about 5.0%, which is larger than that of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 with one layer of Zn atoms and comparable with that of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 with four layers of Zn atoms. The 5.8% expansion ratio is less than the values of graphene-molybdenum disulfide (34%) and poly p -phenylenes (60%) and comparable with the value of Y 2 CF 2 (5.2%) in recent reports. The small volume expansion of Ti 0.75 V 0.75 Cr 0.75 Mo 0.75 C 2 indicates its structural stability with zinc-ion adsorption/desorption, potentially large charge/discharge cycles, and long lifetime, which is significant for rechargeable zinc-ion batteries.…”
Section: Resultssupporting
confidence: 67%
“…This provides an opportunity to build a reliable anode for K ion storage. Li et al applied theoretical calculations to investigate the electrochemical properties of poly­( p -phenylene) for K ion storage. They found that the electron transfer from K to poly­( p -phenylene) enhanced the electrical conductivity and decreased the average OCV.…”
Section: Battery-type Anode Materialsmentioning
confidence: 99%
“…5–9 In addition, the flexible molecular structure of organic materials is beneficial to accommodate large-size K + ions without much spatial hindrance. 10–12 Excellent redox properties and electrochemical performance can be achieved by modifying the functional groups and the structure. 13,14 In the past few decades, various organic electrode materials have been extensively investigated, for example, conductive polymers, 15,16 organic carbonyl compounds, 17,18 organosulfur compounds, 19,20 and organic free-radical compounds.…”
Section: Introductionmentioning
confidence: 99%